Potential Predictors of Long COVID in Italian Children: A Cross-Sectional Survey - Marco Schiavo; Paola Di Filippo; Annamaria Porreca; Giovanni Prezioso; Greta Orlandi; Nadia Rossi; Francesco Chiarelli; Marina Attanasi (MDPI AG, 2024)
Background: Identifying predictive factors of long COVID syndrome (LCS) is essential to preventing and managing this condition. We investigated the prevalence, symptoms, and risk factors of LCS in a cohort of Italian children and adolescents. Methods: We carried out a cross-sectional survey on demographic characteristics and clinical data related to COVID-19 phase and LCS in a cohort of children and adolescents, sending a questionnaire by using the PEDIATOTEM platform. Results: The prevalence of LCS was 25% (99/396). The most frequent symptoms of LCS included nasal congestion, diarrhea, headache, and fatigue. We found no association between demographic data (gender, age, and ethnicity) and LCS. Additionally, we showed that patients with concurrent allergic rhinitis, atopic dermatitis, respiratory disease, gastrointestinal disease, and rheumatologic disease had a higher risk of LCS than patients without those comorbidities. Patients experiencing fatigue, muscle, and abdominal pain in COVID-19 showed a higher risk of LCS than patients complaining of other symptoms. We found no association between vaccination and LCS. Conclusions: Specific comorbidities or symptoms during acute illness were identified as being risk factors for LCS. Understanding which are the risk factors for LCS could yield a clearer picture of its pathogenesis.